Bio-Conversion of Waste Paper Into Fermentable Sugars—A Review - Ojewumi, Modupe E.; Emetere, Moses E.; Obanla, Oyinlola R.; Babatunde, Damilola E.; Adimekwe, Ebuka G. (Frontiers in Chemical Engineering, 2022)
Pollution generated by solid waste has become a massive source of concern for the entire world as the amount of waste being generated worldwide has become overwhelming. The waste paper contributes greatly to the overall solid municipal waste being generated daily and with control methods that are equally bad for the environment or just plain ineffective, the need for better, effective, and environmentally friendly control solutions are required. This paper reviews the use of various microorganisms as they aid in the control of waste papers in an environmentally conscious way. In addition to being an environmentally friendly solution to the issue of solid paper waste pollution, it is also a very prominent source of renewable energy as the conversion of paper into fermentable sugars for the production of bio-ethanol. This review examines the vital revolution in enzymatic hydrolysis of paper to sugar conversion. Salient challenges that involve bioconversion were highlighted and a few solutions were suggested.